Estrategias de marketing para el posicionamiento del producto café del cerro al mercado argentino. - Ugarte Valarezo, Jessenia Nathali (My University, 2018)
Countries around the world support their economic development with exports, which boost the productive apparatus of a nation through the inflow of foreign currency. For this reason, governments should observe international markets and encourage entrepreneurs to export local products. An economic sector with great dynamism is coffee production, which can be given an added value to promote international trade and gains. The obtention of such added value requires a market investigation besides the establishment of consumption levels; an information that assists the development of strategies to position Ecuadorian coffee as a strong competitor in international markets. “Café del Cerro” is a small company located in Zaruma, El Oro, that meets quality standards for exporting. It is a local crop, which after simple processing is sold in major supermarket chains nationwide. In this context, the objective of the present research is to develop positioning strategies for the introduction of “Café del Cerro” in the Argentine market. The transversal descriptive methodology and its bibliographic technique was used, which provided theoretical and statistical information for the development of the research. The main challenge and importance of this case study was to find an international market that demands the Ecuadorian product in mention. Thus, it is worth noting that “Café del Cerro” has a great reception at a local and national level, a situation that favors the export of the product abroad. This is a goal that must be achieved since “Café del Cerro” deserves worldwide recognition for being a high-end quality product.
Los países sustentan su desarrollo económico en el sector exportador, quienes por medio del ingreso de divisas impulsan el aparato productivo de una nación, por esta razón los países deben mirar el mercado internacional e incentivar al empresario a exportar los productos que tiene en su mercado local. Un sector que posee gran dinamismo es el cafetero al que se puede dar un valor agregado para la exportación, conseguirlo requiere de un estudio de mercado, además de establecer los niveles de consumo, información que sirve para elaborar estrategias que permitan posicionarlo en el mercado externo. Café del Cerro es una empresa localizada en el Cantón Zaruma que cumple con los estándares de calidad para la exportación del café, producto que se encuentran a la venta en importantes cadenas de supermercados a nivel nacional. Ante esta realidad se ha formulado como objetivo desarrollar estrategias de posicionamiento para el ingreso del producto Café del Cerro al mercado argentino. La metodología usada fue la descriptiva de tipo transversal y su técnica la bibliográfica, misma que proporcionó información teórica y estadística para el desarrollo de la investigación. La importancia de este caso es encontrar un mercado internacional que demande el producto ecuatoriano, Café del Cerro tiene una gran acogida a nivel local y nacional, situación que favorece a la exportación del producto con vista hacia el mercado internacional como una meta que debe ser alcanzada y darse a conocer a nivel mundial por ser un producto de alta gama y calidad.
Keywords: MERCADO INTERNACIONAL; POSICIONAMIENTO; ESTUDIO DE MERCADO; CONSUMO DE CAFÉ